Powder magnetic core and method for manufacturing powder magnetic core

By using the adhesives containing CR elements and metal magnetic body powder with high FE elements content, combined with liquid CR containing metal soap and resin, the contradiction between the anti -rust resistance of the powder core and the magnetic specialty is solved. Performing and good rust -proof resistance.

CN119365941APending Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047407.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-28
Filing Date
2023-06-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to suppress the reduction of magnetic properties while improving the anti-rust performance of the powdered magnetic core.

Method used

A Cr-containing binder is combined with a metal magnetic powder with a high saturation magnetic flux density and a high Fe content. A liquid Cr-containing metal soap is added to the mixture, and resin is used as the pressure molding process. Binder to form a powder magnetic core with both high magnetic properties and good rust resistance.

Benefits of technology

It is possible to improve the anti-rust performance of the powder magnetic core without reducing the magnetic properties, taking into account the improvement of the magnetic properties and anti-rust properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365941A_ABST
    Figure CN119365941A_ABST
Patent Text Reader

Abstract

The powder magnetic core includes a metal magnetic material powder (11) comprising a plurality of metal magnetic material particles, and a binder (12) that binds the plurality of metal magnetic material particles of the metal magnetic material powder (11) to each other. The binder (12) contains a Cr element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a powder magnetic core and a method for manufacturing the powder magnetic core. Background Art

[0002] Various electronic devices use a step-up / step-down circuit for adjusting a power supply voltage, a DC / DC converter circuit, etc. as a driving circuit of the electronic devices. These circuits use an inductor such as a choke coil and a transformer.

[0003] Hitherto, as an inductor, due to the advantages of DC superposition characteristics, etc., there is a known inductor that uses a powder core made by press-molding a composite magnetic material obtained by mixing metal magnetic powder and a binder. In addition, the powder core is required to have rust resistance from the perspective of long-term maintenance of characteristics and reliability. For example, Patent Document 1 discloses a powder core that uses a composite magnetic material including metal magnetic powder, a binder resin, and a metal soap having a melting point below the thermosetting temperature of the binder resin in order to improve rust resistance.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-41872 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An object of the present disclosure is to provide a powder magnetic core or the like that can achieve both magnetic properties and rust prevention performance.

[0009] Means used to solve problems

[0010] A powder magnetic core according to one embodiment of the present disclosure includes metal magnetic powder composed of a plurality of metal magnetic particles and a binder that binds the plurality of metal magnetic particles of the metal magnetic powder to one another, wherein the binder contains a Cr element.

[0011] In addition, a method for manufacturing a compressed magnetic core in one embodiment of the present invention includes the following steps: a first step of mixing a metal magnetic powder composed of a plurality of metal magnetic particles, a resin and a metal soap to obtain a granulated powder obtained by mixing the aforementioned metal magnetic powder with a binder containing the aforementioned resin and the aforementioned metal soap; and a second step of pressure-molding the obtained aforementioned granulated powder, wherein in the aforementioned first step, the aforementioned metal soap is liquid at 25°C and contains the Cr element.

[0012] Effects of the Invention

[0013] According to the present disclosure, it is possible to achieve both magnetic characteristics and rust prevention performance of the powder magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic perspective view showing the structure of an electric component including the powder magnetic core according to the embodiment.

[0015] Figure 2 It is a diagram schematically showing a cross section of a powder magnetic core according to an embodiment.

[0016] Figure 3 1 is a flowchart showing a method for manufacturing a dust core according to an embodiment.

[0017] Figure 4 3 is a diagram showing a cross-sectional image of the dust core of Evaluation Example 6.

[0018] Figure 5 The graph shows the relationship between the detected amount of Cr or Zn in the powder magnetic core of the evaluation example and the magnetic permeability μ i Ratio relationship diagram.

[0019] Figure 6 The graph shows the relationship between the detected amount of Cr or Zn in the powder magnetic core of the evaluation example and the magnetic permeability μ 85Oe Ratio relationship diagram.

[0020] Figure 7 It is a graph showing the relationship between the detected amount of Cr element or Zn element and the breakdown voltage in the powder magnetic core of the evaluation example. DETAILED DESCRIPTION

[0021] (Until a method of the present disclosure is recognized)

[0022] In recent years, inductors are required to support large currents. To improve DC superposition characteristics, it is effective to increase the ratio of Fe (iron) elements with higher saturation magnetic flux density in the metal magnetic powder contained in the powder core. On the other hand, if the ratio of Fe elements in the metal magnetic powder is increased, rust will occur easily, so the rust prevention performance will decrease.

[0023] Patent document 1 discloses that the rust-proof performance of a powder magnetic core can be improved by coating the portion of a metal magnetic powder that is not covered by a binder resin with a metal soap. However, when the metal magnetic powder is coated with a metal soap as in Patent document 1, the presence of the metal soap increases the spacing between the particles of the metal magnetic powder, and the magnetic properties (e.g., magnetic permeability) of the powder magnetic core decrease. Thus, the inventors of the present application have found that it is difficult to improve the rust-proof performance of a powder magnetic core while suppressing the decrease in magnetic properties in the prior art.

[0024] Therefore, in view of the above problems, the present disclosure provides a powder magnetic core or the like that can achieve both magnetic properties and rust prevention performance by improving rust prevention performance while suppressing a decrease in magnetic properties such as magnetic permeability.

[0025] (Overview of the present disclosure)

[0026] A plurality of examples of the powder magnetic core disclosed in the present invention are shown below.

[0027] <1> A powder magnetic core, comprising:

[0028] Metal magnetic powder composed of a plurality of metal magnetic particles, and

[0029] A binder for binding the plurality of metal magnetic particles of the metal magnetic powder to each other;

[0030] The aforementioned binder contains Cr element.

[0031] <2> according to <1> The powder magnetic core, wherein:

[0032] The ratio of the Cr element in the binder to the total of the Si element, the C element, the O element, the N element, and the Cr element is 0.20 wt % or more and 5.28 wt % or less.

[0033] <3> according to <1> or <2> The powder magnetic core, wherein:

[0034] The content of Fe element in the metal magnetic powder is 90.0 wt % or more.

[0035] <4> according to <3> The powder magnetic core, wherein:

[0036] The content of Fe element in the metal magnetic powder is 99.5 wt % or more.

[0037] In addition, a plurality of examples of the method for manufacturing the dust core of the present disclosure are shown below.

[0038] <5> A method for manufacturing a powder magnetic core, the method comprising the following steps:

[0039] A first step is to mix a metal magnetic powder composed of a plurality of metal magnetic particles, a resin, and a metal soap to obtain a granulated powder in a granular form by mixing the metal magnetic powder with a binder containing the resin and the metal soap; and

[0040] The second step is to pressurize the obtained granulated powder.

[0041] In the first step, the metal soap is liquid at 25° C. and contains the Cr element.

[0042] <6> according to <5> The method for manufacturing a powder magnetic core, wherein:

[0043] In the first step, the ratio of the metal soap in the granulated powder to the metal magnetic powder is 0.1 wt % or more and 2.0 wt % or less.

[0044] <7> according to <5> or <6> The method for manufacturing a powder magnetic core, wherein:

[0045] In the second step, the ratio of the Cr element in the binder of the pressure-molded granulated powder to the total of Si element, C element, O element, N element and Cr element is 0.20 wt % or more and 5.28 wt % or less.

[0046] <8> according to <5> ~ <7> The method for manufacturing a powder magnetic core as described in any one of the preceding claims, wherein:

[0047] In the first step, after obtaining a mixture of the metal magnetic powder and the metal soap, the mixture is mixed with the resin to obtain the granulated powder.

[0048] Hereinafter, embodiments will be described in detail with reference to the drawings.

[0049] It should be noted that the embodiments described below are all specific examples of the present disclosure. The numerical values, shapes, materials, constituent elements, configuration positions of constituent elements, connection forms, steps, and the order of steps given in the following embodiments are all examples and are not intended to limit the present disclosure. In addition, the constituent elements not described in the independent claims among the constituent elements of the following embodiments are described as optional constituent elements.

[0050] In addition, each figure is a schematic diagram and is not necessarily a strict illustration. Therefore, for example, the scales in each figure are not necessarily the same. In addition, in each figure, substantially the same structure is marked with the same symbol, and repeated descriptions are omitted or simplified.

[0051] In addition, in this specification, terms such as parallel or orthogonal that indicate the relationship between elements, terms such as rectangle or cuboid that indicate the shape of elements, and numerical ranges are not expressions that express only strict meanings, but rather expressions that indicate substantially equivalent ranges, for example, also including differences of about several percent.

[0052] (Implementation Method)

[0053] [constitute]

[0054] First, regarding an electrical component as an example of use of the powder magnetic core according to the embodiment, refer to Figure 1 and Figure 2Provide explanation.

[0055] Figure 1 It is a schematic perspective view showing the structure of an electric component including the powder magnetic core according to the embodiment. Figure 1 The schematic shape of the powder core 10 described later is shown, and the inside of the powder core 10 is transparently shown. For example, components such as the coil member 40 that are buried in the powder core 10 and hidden are shown with dotted lines, and are expressed as being visible through the powder core 10 .

[0056] like Figure 1 As shown, the electric component 100 includes a powder magnetic core 10 , a coil member 40 , a first terminal member 25 , and a second terminal member 35 .

[0057] The electrical component 100 is, for example, a rectangular inductor, and its general shape is determined by the shape of the powder core 10. It should be noted that the powder core 10 can be formed into any shape by press molding. That is, the electrical component 100 of any shape can be realized according to the shape of the powder core 10 during press molding. Therefore, the shape of the powder core is not limited to a rectangular parallelepiped, and can be other shapes.

[0058] The electric component 100 is a passive element that accumulates the electric energy flowing between the first terminal member 25 and the second terminal member 35 as magnetic energy through the coil member 40. In this embodiment, the electric component 100 is described as one of the use examples of the powder core 10, but the powder core 10 can be used simply as a magnetic material, and the use example is not limited to the electric component 100 of this embodiment. The powder core 10 can be used for a desired purpose that can effectively utilize the characteristics of a magnetic material that takes both magnetic properties and rust prevention performance into consideration.

[0059] The powder core 10 has rectangular opposing faces formed respectively on the first terminal member 25 and the second terminal member 35, and is in the shape of a generally quadrangular prism in which the four sides of each opposing face are connected by a top face, a bottom face, and two side faces. In the present embodiment, the powder core 10 is, for example, in the shape of a rectangle with a bottom face and a top face having a size of about 14.0 mm×12.5 mm, and the spacing distance from the bottom face to the top face is about 8.0 mm.

[0060] Figure 2 1 is a diagram schematically showing a cross section of the powder magnetic core 10 . Figure 2 This is an enlarged view of a part of the cross section of the powder magnetic core 10 .

[0061] like Figure 2 As shown, the powder magnetic core 10 includes a metal magnetic powder 11 composed of a plurality of metal magnetic particles, and a binder 12 that binds the plurality of metal magnetic particles of the metal magnetic powder 11 to each other.

[0062] Metal magnetic powder 11 may be made of, for example, a metal magnetic powder containing Fe as a main component. Metal magnetic powder 11 has a higher saturation magnetic flux density than magnetic powders such as ferrite, and is therefore useful for use at high currents.

[0063] The content of Fe element in metal magnetic powder 11 is, for example, 90.0 wt % or more. This increases the saturation magnetic flux density of metal magnetic powder 11 and improves the magnetic permeability of powder magnetic core 10 .

[0064] Metal magnetic powder 11 may contain elements other than Fe. Examples of elements other than Fe contained in metal magnetic powder 11 include Si (silicon) element, Al (aluminum) element, Cr (chromium) element, and B (boron) element.

[0065] From the perspective of further improving the magnetic permeability of the powder magnetic core 10, the content of Fe in the metal magnetic powder 11 may be 99.5 wt% or more. The metal magnetic powder 11 having a content of Fe of 99.5 wt% or more is formed, for example, of Fe and inevitable impurities. Examples of the inevitable impurities include Mn (manganese) element, Ni (nickel) element, P (phosphorus) element, S (sulfur) element, C (carbon) element, and O (oxygen) element.

[0066] The method for producing the metal magnetic powder 11 is not particularly limited, and various atomization methods, various chemical methods, or various pulverization methods may be used.

[0067] When producing metal magnetic powder 11 containing 99.5 wt % or more of Fe, for example, a carbonyl method, a spray method, or an electrolytic method may be used. From the perspective of magnetic properties, metal magnetic powder 11 may be carbonyl iron powder produced by a carbonyl method.

[0068] The median particle size D50 of the metal magnetic powder 11 is, for example, not less than 1.0 μm and not more than 35 μm. Since the electric field concentration between particles can be alleviated, insulation can be ensured by constructing the metal magnetic powder 11 in a manner in which the median particle size D50 is small. In addition, by adopting the above-mentioned median particle size D50, a high filling rate and handling properties can be ensured. In addition, by making the median particle size D50 of the metal magnetic powder 11 less than 35 μm, the core loss in the high-frequency region, especially the eddy current loss, can be reduced. It should be noted that the median particle size D50 of the metal magnetic powder 11 is the particle size when the cumulative value reaches 50% of the total by counting the particle sizes from small to large using a particle size distribution meter measured by a laser diffraction scattering method.

[0069] The binder 12 is provided so as to cover the periphery of the metal magnetic powder 11. The binder 12 is located between the metal magnetic particles of the metal magnetic powder 11. The binder 12 is an insulating resin material having a resin as a main component. The binder 12 is formed, for example, of a resin and a metal soap. The binder 12 may also contain a coupling agent and insulating particles (for example, inorganic particles such as talc).

[0070] The resin is, for example, a thermosetting resin. Examples of thermosetting resins include epoxy resins, phenolic resins, silicone resins, and polyimide resins. The resin may be a thermoplastic resin. Examples of thermoplastic resins include acrylic resins, polyethylene, polypropylene, and polystyrene. The binder 12 may include a variety of resins.

[0071] The binder 12 contains Cr element. In the binder 12, for example, a component containing Cr element is dispersed in the resin. By dispersing the component containing Cr element in the resin, while showing the effect of improving the rust resistance based on the Cr element, the Cr element uniformly attracts the metal magnetic particles and the resin, thereby suppressing the reduction of the magnetic properties of the powder magnetic core 10. The Cr element contained in the binder 12 is derived from, for example, a metal soap. The binder 12 contains, for example, a metal soap containing Cr element and / or a reactant of a metal soap containing Cr element as a component containing Cr element.

[0072] The ratio of the Cr element in the binder 12 to the sum of the Si element, the C element, the O element, the N (nitrogen) element, and the Cr element is, for example, 0.20 wt% or more and 5.28 wt% or less. Thus, it is possible to improve the rust resistance while suppressing the reduction in the magnetic properties of the effective powder magnetic core 10. In addition, from the perspective of further suppressing the reduction in the magnetic properties of the powder magnetic core 10, the ratio of the Cr element may be 1.08 wt% or more and 5.28 wt% or less.

[0073] Si, C, O, and N are elements that are easily detected by elemental analysis, and are main elements contained in a resin used in a conventional adhesive 12. Therefore, the ratio of Cr is an indicator showing the content of Cr in the adhesive 12.

[0074] The method for measuring the ratio of the Cr element in binder 12 is not particularly limited, and the ratio can be calculated based on, for example, elemental analysis of the metal magnetic particles of metal magnetic powder 11 in an image of a cross section of powder core 10 .

[0075] Specifically, first, Si, C, O, N, and Cr are detected on a weight basis at 15 measurement points between the metal magnetic particles of the metal magnetic powder 11 in the image of the cross section of the pressed powder core 10. Then, the average value of the ratio of the Cr element to the Si element, C element, O element, N element, and Cr element at each measurement point is calculated. The calculated value is used as the ratio of the Cr element in the binder 12. It should be noted that, in the measurement point, if the ratio of elements other than Si, C, O, N, and Cr in the elemental analysis is high, the measurement point can be excluded from the calculation of the average value. For example, the detection result of the measurement point where the ratio of the Fe element derived from the metal magnetic powder 11 is as high as or above a predetermined threshold value is excluded from the calculation of the average value. The predetermined threshold value is, for example, 88.0wt%. In addition, the number of the above-mentioned measurement points is only an example, and the measurement points are not limited to 15. For example, the measurement points can be N (N is, for example, an integer greater than 10).

[0076] The image of the cross section of the powder core 10 is, for example, a scanning electron microscope (SEM (Scanning Electron Microscope)) image. The detection of the elements at each measurement point is performed, for example, using an energy dispersive X-ray (EDX (Energy Dispersive X-ray)) spectrometer. For example, the weight-based detection amount of each element is calculated based on the intensity of the peak corresponding to each element in the EDX spectrum obtained at each measurement point using scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX).

[0077] The cross section of the powder core 10 can be formed by a conventional cross section formation method in SEM image observation. For example, the powder core 10 is embedded in a resin or the like, cut, and then ion milled to obtain the cross section of the powder core 10 for observation.

[0078] For the cross-sectional image used for detecting the element at each measuring point, for example, an image obtained by photographing an area of ​​15 μm×15 μm or more and 50 μm×50 μm or less is used. The magnification of the cross-sectional image is, for example, 1000 times or more and 7000 times or less. The 15 measuring points are selected from the metal magnetic particles of the different combinations of metal magnetic powders 11. In addition, in the case of a measuring point containing a ratio of Fe element derived from the metal magnetic powder 11 that is higher than a predetermined threshold value as described above, when the number of such measuring points exceeds half of all the measuring points, the result at this time is not adopted and re-measurement is performed.

[0079] In the powder magnetic core 10 , the ratio of the binder 12 to the metal magnetic powder 11 is, for example, 1 wt % or more and 10 wt % or less.

[0080] Next, refer to Figure 1 , while the coil member 40, the first terminal member 25 and the second terminal member 35 are described.

[0081] The coil member 40 is wound with a long conductor covered with an insulating film, i.e., a wire (winding portion), and the two ends of the wire are connected to the first terminal member 25 and the second terminal member 35, respectively (lead portions 20 and 30). This embodiment describes a method of using a round wire with a cross-sectional diameter of about 0.65 mm as a wire. It should be noted that there is no particular limitation on the thickness and shape of the wire. As long as the thickness can be wound, a round wire and a flat wire with a rectangular cross section can be appropriately selected. The winding portion is buried near the center of the powder core 10. In addition, in the lead portions 20 and 30, the two ends of the wire extend continuously from the winding portion toward each opposite surface, respectively, protruding from the outside of the powder core 10. Here, a portion of the lead portion is stretched in a manner to form a flat shape and bent along the opposite surface and the bottom surface. In the portion stretched in this way, the insulating film coating is peeled off, and it becomes possible to be electrically connected to the outside.

[0082] The first terminal member 25 and the second terminal member 35 are formed of a conductor plate such as a phosphor bronze material or a copper material. The first terminal member 25 and the second terminal member 35 are respectively formed in a manner that has a recessed portion near the center along the opposing surfaces and is sunken into the powder core 10. Lead portions 20 and 30 are arranged outside the recessed portion. The lead portion 20 is electrically connected to the first terminal member 25. The lead portion 30 is electrically connected to the second terminal member 35. The lead portions 20 and 30 are connected to the first terminal member 25 and the second terminal member 35 by resistance welding or the like. In addition, the first terminal member 25 and the second terminal member 35 are bent in a manner that they are inserted into the interior of the powder core 10, and the first terminal member 25 and the second terminal member 35 are fixed to the powder core 10 when the powder core 10 is inserted into the bent portion.

[0083] Furthermore, the first terminal member 25 and the second terminal member 35 are bent along the bottom surface of the powder core 10 together with the lead portions 20 and 30. Thus, the lead portions 20 and 30 are bent and fixed to the bottom side of the electric component 100 while being held by the first terminal member 25 and the second terminal member 35. That is, the lead portions 20 and 30 can be directly connected to a connection pad (not shown) such as a mounting substrate on which the electric component 100 will be mounted in the future.

[0084] It should be noted that the first terminal member 25 and the second terminal member 35 are not essential components. As long as the lead portions 20 and 30 have strength to maintain their shapes, the first terminal member 25 and the second terminal member 35 may not be provided.

[0085] As described above, the powder core 10 of the present embodiment includes the metal magnetic powder 11 and the binder 12 containing the Cr element. Thus, the binder 12 containing the Cr element covers the metal magnetic particles of the metal magnetic powder 11, thereby improving the corrosion resistance of the metal magnetic powder 11. In addition, the Cr element in the binder 12 attracts the binder 12 and the metal magnetic particles of the metal magnetic powder 11, thereby reducing the interval between the metal magnetic particles. Thus, the magnetic properties and rust prevention performance of the powder core 10 can be achieved at the same time.

[0086] [Manufacturing method]

[0087] Next, regarding an example of a method for manufacturing the above-mentioned powder magnetic core 10, refer to Figure 3 Provide explanation.

[0088] Figure 3 1 is a flowchart showing a method for manufacturing a dust core according to an embodiment.

[0089] In the manufacture of the powder core 10 in the present embodiment, first, the metal magnetic powder 11 and the metal soap are mixed (step S11). Thus, a mixture of the metal magnetic powder 11 and the metal soap is obtained. In step S11, the mixture does not substantially contain a resin.

[0090] The metal soap contains Cr element. Specifically, the metal soap is fatty acid chromium. In addition, the metal soap is liquid at 25°C (normal temperature). That is, the melting point of the metal soap is lower than 25°C. Therefore, in step S11, the metal magnetic powder 11 is mixed with the liquid metal soap. The liquid metal soap has a branch on the hydrocarbon chain of the fatty acid in order to lower the melting point. The metal soap is manufactured, for example, by a direct method or a double decomposition method. The direct method is a method of directly reacting a fatty acid with a metal oxide or a metal hydroxide. The double decomposition method is a method of reacting an alkaline compound with a fatty acid in an aqueous solution state to form an alkaline compound of a fatty acid, and further reacting it with a metal salt containing a metal or a semimetal.

[0091] By mixing metal magnetic powder 11 and liquid metal soap before mixing with the resin, the surfaces of the metal magnetic particles of metal magnetic powder 11 and the hydrophilic part of the metal soap can react easily, and the metal soap can function effectively.

[0092] Next, a resin is further added to the mixture obtained in step S11, and the mixture and the resin are mixed (step S12). Thus, a granulated powder in the form of a mixture of metal magnetic powder 11 and binder 12 containing a resin and a metal soap is obtained.

[0093] The resin mixed in step S12 is used in a state of being dissolved in a solvent that can dissolve the resin, such as isopropyl alcohol, acetone, toluene, xylene, ethanol, or methyl ethyl ketone. It should be noted that the resin mixed in step S12 may not be dissolved in the solvent.

[0094] After the mixture obtained in step S11 is mixed with a resin, the solvent is evaporated by heating at a temperature of 65°C or higher and 150°C or lower, and the mixture is pulverized to obtain a granular granulated powder (composite magnetic material) with good formability. Furthermore, the granulated powder can be classified to obtain a granulated powder with a particle size uniformly within a predetermined range. Thus, the formability can be further improved.

[0095] The mixing in step S11 and step S12 is performed using, for example, a mortar, a stirrer, a ball mill, a V-type mixer, or a cross-rotating machine.

[0096] In step S11 and / or step S12, other materials such as a coupling agent and insulating particles may be further added and mixed as necessary.

[0097] Thus, in step S11 and step S12, metal magnetic powder 11, resin and metal soap are mixed to obtain granulated powder in the form of a granule in which metal magnetic powder 11 and binder 12 containing resin and metal soap are mixed. The step including step S11 and step S12 is an example of the first step.

[0098] The ratio of the metal soap in the granulated powder to the metal magnetic powder 11 (i.e., the amount of the metal soap added to the amount of the metal magnetic powder 11 added) is, for example, 0.1 wt% or more and 2.0 wt% or less. This can effectively suppress the reduction in the magnetic properties of the powder magnetic core 10 while improving the rust prevention performance. In addition, from the perspective of further suppressing the reduction in the magnetic properties of the powder magnetic core 10, the ratio of the metal soap can be 0.5 wt% or more and 2.0 wt% or less.

[0099] The ratio of the resin in the granulated powder to the metal magnetic powder 11 (that is, the amount of the resin added to the amount of the metal magnetic powder 11 added) is, for example, 1 wt % or more and 10 wt % or less.

[0100] It should be noted that the mixing of the metal magnetic powder 11, the resin and the metal soap is divided into step S11 and step S12, but is not limited thereto. As long as a granulated powder obtained by mixing the metal magnetic powder 11 with the binder 12 containing the resin and the metal soap can be obtained, the mixing step of the metal magnetic powder 11, the resin and the metal soap may be different from the above. For example, the metal magnetic powder 11, the resin and the metal soap may be mixed at once. In addition, the combination of materials different from the above may be divided into two or more steps for mixing.

[0101] Next, the granulated powder obtained in step S12 is put into a mold and pressed into a desired shape to obtain a powder core 10 (step S13). Step S13 is an example of the second step. Step S13 is, for example, 3 ton / cm 2 Above 7ton / cm 2 The pressure molding is performed at a pressure in the following range. The pressed powder magnetic core 10 is subjected to a curing treatment, for example, by heating. The curing treatment conditions are set according to the type of resin used.

[0102] The ratio of Cr in the binder 12 in the pressurized granulated powder to the total of Si, C, O, N and Cr is, for example, 0.20 wt % or more and 5.28 wt % or less. This can effectively suppress the deterioration of the magnetic properties of the powder magnetic core 10 while improving the rust resistance.

[0103] The powder core 10 is manufactured through these steps S11 to S13. The manufactured powder core 10 is used as a part of the electric component 100 in which the coil is embedded. In addition, the granulated powder and the coil member 40 may be pressure-molded together.

[0104] As described above, the method for manufacturing the powder core 10 includes the following steps: a first step of mixing a metal magnetic powder 11, a resin, and a metal soap to obtain a granulated powder obtained by mixing the metal magnetic powder 11 and a binder 12 containing the resin and the metal soap (steps S11 and S12); and a second step of press-molding the obtained granulated powder (step S13). In the first step, the metal soap is liquid at 25°C and contains the Cr element.

[0105] Thus, the Cr element of the metal soap reacts with the metal magnetic powder 11, and the corrosion resistance of the metal magnetic powder 11 to rust can be improved. In addition, since the metal soap is in a liquid state when mixed, the metal soap is dispersed in the resin and easily exists evenly in the resin and at the interface between the resin and the metal magnetic powder 11. Therefore, the intervals between the metal magnetic particles of the metal magnetic powder 11 are not easy to expand. As a result, even if the metal soap is added, the magnetic properties of the manufactured powder magnetic core 10 can be suppressed from being reduced. Therefore, it is possible to achieve both the magnetic properties and the rust prevention performance of the manufactured powder magnetic core 10.

[0106] [Evaluation of powder cores]

[0107] Next, the evaluation results of the powder magnetic core of the embodiment will be described. Specifically, the powder magnetic core was produced as follows, and the produced powder magnetic core was analyzed and evaluated for its characteristics. It should be noted that the present embodiment is not limited to the following evaluation at all.

[0108] <Production of powder core>

[0109] First, the preparation of the powder magnetic core used for the evaluation will be described. Evaluation Examples 1 to 10 were prepared using the production method described in the above [Production Method]. The specific method is as follows.

[0110] First, metal magnetic powder, resin, and metal soap are prepared.

[0111] The metal magnetic powder used has an Fe content of 99.5 wt % or more.

[0112] The resin used was a modified silicone resin (concentration 50 wt%) having methyl and phenyl groups in the side chain, which was preliminarily dissolved in a solvent (isopropyl alcohol). The amount of the resin added was 3 wt % relative to the amount of the metal magnetic powder added. It should be noted that the amount of the resin added was the amount by weight excluding the solvent.

[0113] In Evaluation Examples 2 to 7, a fatty acid chromium which is liquid at 25°C is used as the metal soap. In Evaluation Examples 8 to 10, a fatty acid zinc which is solid at 25°C is used as the metal soap. The amount of metal soap added relative to the amount of metal magnetic powder added is the amount (wt%) shown in Table 2. Hereinafter, the metal soap containing the Cr element used in Evaluation Examples 2 to 7 may be referred to as "Cr metal soap", and the metal soap containing the Zn element used in Evaluation Examples 8 to 10 may be referred to as "Zn metal soap". In addition, in Evaluation Example 1, a powder magnetic core was produced without adding a metal soap.

[0114] Using these materials, metal magnetic powder and metal soap are mixed, and then a resin is added and mixed, and the mixture is heated to remove the solvent, thereby preparing a granulated powder. In addition, as a mixing method, mixing is performed using a mortar.

[0115] The granulated powder was heated to 4 ton / cm at room temperature. 2 The annular magnetic core was pressed with a pressure of 10.3 mm and an annular magnetic core with an outer diameter of 14.4 mm, an inner diameter of 10.3 mm and a thickness of 4.4 mm was produced for evaluation of magnetic permeability. The annular magnetic core was then dried at 150° C. for 2 hours to solidify the binder, thereby producing an annular powder magnetic core.

[0116] In addition, the prepared granulated powder was heated to 4 ton / cm at room temperature. 2The plate-shaped compact was pressed with a pressure of 1000 g to produce a plate-shaped compact with a length of 12 mm, a width of 12 mm and a thickness of 0.70 mm for evaluation of breakdown voltage. The plate-shaped compact was then dried at 150° C. for 2 hours to solidify the binder, thereby producing a plate-shaped powder core.

[0117] In addition, the prepared granulated powder was heated to 4 ton / cm at room temperature. 2 The plate-shaped compact was press-formed with a pressure of 1000 g to evaluate the rust-proof performance, and a plate-shaped compact with a length of 12 mm, a width of 12 mm, and a thickness of 4.1 mm was produced. The plate-shaped compact was then dried at 150° C. for 2 hours to solidify the binder, thereby producing a plate-shaped powder magnetic core.

[0118] <Calculation method of magnetic permeability>

[0119] The magnetic permeability is obtained as follows: For the annular pressed powder core, the inductance L at 0A is measured using an LCR meter, and the magnetic permeability μ (measurement frequency 100kHz) is calculated using the following formula (1). The inductance L is measured under the conditions of applying a magnetic field of 0Oe and 85Oe, and the magnetic permeability μ calculated from the inductance L under each condition is recorded as the magnetic permeability μ i and magnetic permeability μ 85Oe Magnetic permeability μ i Also called initial permeability.

[0120] μ=(L×le) / (μ0×Ae×n 2 ) (1)

[0121] It should be noted that le represents the effective magnetic path length, μ0 represents the magnetic permeability of vacuum, Ae represents the cross-sectional area, and n represents the number of turns of the measuring coil.

[0122] In addition, the magnetic permeability in Evaluation Example 1 was used as a reference, and the ratio of the magnetic permeability of each Evaluation Example to the magnetic permeability of Evaluation Example 1 was calculated. The ratio of the magnetic permeabilities calculated from the inductance L under the applied magnetic field of 0 Oe was recorded as the magnetic permeability μ i The ratio of the magnetic permeability calculated from the inductance L under the applied magnetic field of 85 Oe is recorded as the magnetic permeability μ 85Oe For example, the magnetic permeability μ of Evaluation Example 2 is i Ratio (magnetic permeability μ of Evaluation Example 2 i ) / (magnetic permeability μ of evaluation example 1 i ), the magnetic permeability μ of Evaluation Example 2 85Oe Ratio is (the magnetic permeability μ in Evaluation Example 2 85Oe ) / (magnetic permeability μ in Evaluation Example 1 85Oe ). The higher the magnetic permeability ratio, the better the magnetic properties.

[0123] <Evaluation Method of Breakdown Voltage>

[0124] The breakdown voltage as an insulation index is determined by clamping the produced plate-shaped powder core with conductive rubber disposed on both main surfaces, applying a DC voltage of an initial value of 10V, and then continuously increasing the applied voltage value at a rate of 5V / min. The value (V / mm) obtained by dividing the applied voltage value just before insulation breakdown by the thickness of the molded body is used as the breakdown voltage value of each powder core. A high breakdown voltage value indicates high insulation. In addition, by increasing the insulation, the leakage current of the metal magnetic powder (the resulting eddy current loss) can be suppressed, and the magnetic properties are improved.

[0125] <Evaluation method of rust prevention performance>

[0126] Evaluation of Rust Prevention Performance The powder core was placed in a high temperature hygrostat maintained at 65° C. and 90% RH, and the surface of the powder core was visually observed for rust after 200 hours, and evaluated according to the following criteria.

[0127] ○: No rust was observed

[0128] ×: Rust was observed

[0129] <Elemental Analysis>

[0130] The produced plate-shaped powdered magnetic core was embedded in a resin and cut, and then a cross section for observation was formed by ion milling. The element analysis of the powdered magnetic core was performed based on the image of the formed cross section using SEM-EDX. Specifically, 15 points between the particles of the metal magnetic powder (i.e., the positions where the binder exists) were selected as measurement points in the image of the formed cross section so as to be distributed over the entire image, and each element was detected on a weight basis based on the EDX spectrum obtained at each measurement point. Figure 4 3 is a diagram showing a cross-sectional image of the dust core of Evaluation Example 6. Figure 4 is a SEM image of a cross section formed by the above method. Figure 4 The SEM images shown have a magnification of 5000 times. Figure 4 The black area in the image is the adhesive, and the white cross marked in the black area is the measurement point. Figure 4 As shown in FIG. 1 , the positions of 15 measurement points are determined in such a way that the measurement points between the metal magnetic particles of the different metal magnetic powders are formed. In addition, the size of the area to be measured at each measurement point is 393.6 nm. 2 For the powder cores other than Evaluation Example 6, element analysis was performed in the same manner.

[0131] Based on the elemental analysis results, the content of Cr and Zn at each measuring point is calculated. The content of Cr at each measuring point is the ratio (wt%) of Cr to the total of Si, C, O, N and Cr calculated based on the elemental analysis results. The content of Zn at each measuring point is the ratio (wt%) of Zn to the total of Si, C, O, N and Zn calculated based on the elemental analysis results.

[0132] Table 1 shows the detected amount of Cr element at each measuring point of Evaluation Example 6. In the elemental analysis, Fe element which is considered to be derived from the metal magnetic powder present in the depth direction of the cross section was also detected, and the detected amount of Fe element is also shown in Table 1. The detected amount of Fe element at each measuring point in Table 1 adopts the ratio (wt%) of Fe element to the total of Si element, C element, O element, N element, Cr element and Fe element calculated based on the elemental analysis results.

[0133] Table 1

[0134]

[0135] As shown in Table 1, at the measurement point where the detection amount of the Fe element is large, the result obtained is that the detection amount of the Cr element also increases. In the EDX spectrum, when the detection amount of the Fe element is large, the detection accuracy of other elements is reduced due to the influence of the Fe element, and it is particularly difficult to detect the Si element, the C element, and the O element, so the detection amount of the Cr element also increases. Therefore, among the 15 measurement points, the average value of the Cr detection amount excluding the data of the measurement point where the detection amount of the Fe element exceeds 88.0wt% (the data of the measurement points 8, 14, and 15 marked with underlines in Table 1) is used as the detection amount of the Cr element in the binder of each evaluation example.

[0136] As with the detected amount of Cr, the average value of the detected amount of Zn excluding the data of the measurement point where the detected amount of Fe exceeded 88.0 wt % was taken as the detected amount of Zn in the binder of each evaluation example.

[0137] In addition, regarding the evaluation examples other than the evaluation example 6, the detected amount of the Cr element and the detected amount of the Zn element in the binder were calculated by the same method as that of the evaluation example 6.

[0138] <Analysis and Evaluation Results>

[0139] The dust cores of Evaluation Examples 1 to 10 were analyzed and evaluated by the above method. The results are shown in Table 2. Table 2 shows the amount of resin added, the type and amount of metal soap added, the amount of Cr and Zn detected in the binder, and the magnetic permeability μ of the dust cores of Evaluation Examples 1 to 10. i Specific, magnetic permeability μ 85Oe The evaluation results of ratio, breakdown voltage and anti-rust performance.

[0140] also, Figure 5 The results show the detected amount of Cr or Zn in the powder magnetic cores of the evaluation examples shown in Table 2 and the magnetic permeability μ i In addition, Figure 6 The results show the detected amount of Cr or Zn in the powder magnetic cores of the evaluation examples shown in Table 2 and the magnetic permeability μ 85Oe In addition, Figure 7 2 is a graph showing the relationship between the detected amount of Cr element or Zn element in the powder magnetic core of the evaluation example shown in Table 2 and the breakdown voltage. Figure 5 to Figure 7 In the figure, the data of Evaluation Example 1 without adding metal soap are indicated by circles, the data of Evaluation Examples 2 to 7 with adding Cr metal soap are indicated by squares, and the data of Evaluation Examples 8 to 10 with adding Zn metal soap are indicated by triangles. Figure 5 to Figure 7 The horizontal axis in shows the detected amount of Cr element for Evaluation Examples 2 to 7, and shows the detected amount of Zn element for Evaluation Examples 8 to 10.

[0141]

[0142] As shown in Table 2, in Evaluation Example 1 to which no metal soap was added, rust was observed in the evaluation of the rust prevention performance, indicating that rust occurred. On the other hand, in the powder magnetic cores of Evaluation Examples 2 to 10 to which metal soap was added, rust was not observed, indicating that the rust prevention performance was improved. It is considered that in Evaluation Examples 8 to 10, the solid film formed on the surface of the metal magnetic particles of the metal magnetic powder by the Zn metal soap which is solid at room temperature improves the rust prevention performance. In addition, it is considered that in Evaluation Examples 2 to 7, the Cr element with high corrosion resistance to rust in the Cr metal soap which is liquid at room temperature reacts on the surface of the metal magnetic powder, improving the rust prevention performance of the metal magnetic powder.

[0143] In addition, as shown in Table 2, Figure 5 and Figure 6 As shown in FIG. 1 , the detected amount of Zn element in the powder magnetic cores of Evaluation Examples 8 to 10 to which Zn metal soap was added increased, and the magnetic permeability μ i Specific and permeability μ 85Oe Ratio reduction (in Figure 5 and Figure 6 In contrast, the powder cores of Evaluation Examples 2 to 7 to which Cr metal soap is added do not have a monotonic change in magnetic permeability μ as in Evaluation Examples 8 to 10 as the detected amount of Cr element increases. i Specific and permeability μ 85Oe In particular, the magnetic permeability μ of the powder cores of Evaluation Examples 2 to 6 is lower than that of the powder cores of Evaluation Examples 8 to 10. i Specific and permeability μ 85Oe The detected amount of Cr in the binder is in the range of 0.20wt% to 5.28wt%. The increase of the detected amount of Cr and the magnetic permeability μ i Specific and permeability μ 85Oe The ratio increases. This is considered to be because the Cr metal soap dispersed in the resin has a Cr portion with high affinity to the metal magnetic powder and a fatty acid portion with high affinity to the resin, thereby attracting the resin and the metal magnetic powder and reducing the spacing between the metal magnetic particles of the metal magnetic powder. On the other hand, it is considered that in Evaluation Examples 8 to 10, the Zn metal soap forms a film on the surface of the metal magnetic particles of the metal magnetic powder, the spacing between the metal magnetic particles is expanded, the detection amount of the Zn element is increased, and the magnetic permeability μ is increased. i Specific and permeability μ 85Oe Than decreased.

[0144] In addition, as shown in Table 2 and Figure 7 As shown in the figure, the detected amount of Cr element in the powder cores of Evaluation Examples 2 to 7 to which Cr metal soap is added increases, and the breakdown voltage increases. In other words, the amount of Cr metal soap added increases, and the breakdown voltage increases. This is considered to be because the dispersibility of the resin is improved by adding Cr metal soap. On the other hand, the powder cores of Evaluation Examples 8 to 10 to which Zn metal soap is added have a basically constant breakdown voltage (at 2.5°C) regardless of the detected amount of Zn element. Figure 7 Indicated by double-dotted lines).

[0145] <Conclusion>

[0146] According to the results of the above analysis and evaluation of the pressed powder core, it was found that the pressed powder core using the binder containing the Cr element did not rust, suppressed the decrease in magnetic permeability, increased the breakdown voltage, and was able to take into account both magnetic properties and rust prevention performance. For example, when the pressed powder core using the binder containing the Cr element is used for an inductor, even if a metal magnetic powder with a high saturation magnetic flux density of 99.5wt% or more of Fe is used, rust can be suppressed, the DC superposition characteristics of the high saturation magnetic flux density can be reflected, and the eddy current loss can be reduced. In particular, when the ratio of the metal soap containing the Cr element to the metal magnetic powder is 0.1wt% or more and 2.0wt% or less, and the content of the Cr element in the binder of the manufactured pressed powder core is 0.20wt% or more and 5.28wt% or less, the detected amount of the Cr element increases, and the magnetic permeability increases, which can effectively suppress the decrease in magnetic properties.

[0147] In contrast, the powder core using a binder containing no metal soap rusted and had low rust resistance. In addition, the powder core using a binder containing Zn metal soap did not rust, but the decrease in magnetic permeability could not be suppressed and the breakdown voltage (insulation) also increased.

[0148] (Other Implementations, etc.)

[0149] As mentioned above, although the powder magnetic core etc. which concern on embodiment of this disclosure are demonstrated, this disclosure is not limited to this embodiment.

[0150] For example, electrical components using the above-mentioned powder magnetic core are also included in the present disclosure. Examples of electrical components include high-frequency reactors, inductors, transformers and other inductance components. In addition, power supply devices having the above-mentioned electrical components are also included in the present disclosure.

[0151] In addition, the present disclosure is not limited to the above-mentioned embodiments. Without departing from the gist of the present disclosure, various modifications that can be conceived by those skilled in the art may be applied to the present embodiments, and various combinations of components in different embodiments may also fall within the scope of one or more embodiments.

[0152] Industrial Applicability

[0153] The powder magnetic core disclosed in the present invention can be applied to materials for magnetic cores of high-frequency inductors and transformers, and the like.

[0154] Explanation of symbols

[0155] 10 Powdered Magnetic Core

[0156] 11 Metal magnetic powder

[0157] 12 Binder

[0158] 20, 30 Lead wire

[0159] 251st terminal member

[0160] 35 2nd terminal member

[0161] 40 Coil components

[0162] 100 Electrical components

Claims

1. A powder magnetic core, comprising: Metal magnetic powder composed of a plurality of metal magnetic particles, and a binder for binding the plurality of metal magnetic particles of the metal magnetic powder to each other; The binder contains Cr element.

2. The powder magnetic core according to claim 1, wherein: The ratio of the Cr element in the binder to the total of the Si element, the C element, the O element, the N element, and the Cr element is 0.20 wt % or more and 5.28 wt % or less.

3. The powder magnetic core according to claim 1 or 2, wherein: The content of Fe element in the metal magnetic powder is 90.0 wt % or more.

4. The powder magnetic core according to claim 3, wherein: The content of Fe element in the metal magnetic powder is 99.5 wt % or more.

5. A method for manufacturing a powder magnetic core, the method comprising the following steps: A first step is to mix a metal magnetic powder composed of a plurality of metal magnetic particles, a resin, and a metal soap to obtain a granulated powder in a granular form by mixing the metal magnetic powder with a binder containing the resin and the metal soap; and The second step is to pressurize the obtained granulated powder. In the first step, the metal soap is liquid at 25° C. and contains the Cr element.

6. The method for manufacturing a powder magnetic core according to claim 5, wherein: In the first step, the ratio of the metal soap in the granulated powder to the metal magnetic powder is 0.1 wt % or more and 2.0 wt % or less.

7. The method for manufacturing a powder magnetic core according to claim 5, wherein: In the second step, the ratio of the Cr element in the binder of the pressure-molded granulated powder to the total of Si element, C element, O element, N element and Cr element is 0.20 wt % or more and 5.28 wt % or less.

8. The method for producing a powder magnetic core according to any one of claims 5 to 7, wherein: In the first step, after obtaining a mixture of the metal magnetic powder and the metal soap, the mixture is mixed with the resin to obtain the granulated powder.

Citation Information

Patent Citations

  • Composite magnetic material, composite magnetic compact obtained by thermally curing the same, electronic component arranged by use of composite magnetic compact, and manufacturing methods thereof

    JP2018041872A